2018
DOI: 10.4066/biomedicalresearch.29-18-830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D MR imaging sequences in knee articular cartilage at 1.5 T

Abstract: Purpose: To compare 3D high-resolution MRI sequences in term of contrast, Signal to Noise Ratio (SNR), artefacts and cartilage thickness in knee articular cartilage at 1.5 T. Materials and methods: Fourteen healthy volunteers and seven patients underwent articular knee cartilage exam. The 3D sequences were VOLUME Imaging with Body Enhancement (VIBE), True Fast Imaging with Steady-state Precession (TRUEFISP), Dual Echo Steady State (DESS), Multi Echo Data Image Combination (MEDIC) and Sampling Perfection with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…Hence, 3D water excitation sequence was found to be better than 2D fat suppression sequence for cartilage over lateral tibial plateau. This study correlates well with the study done by Mokhtar Mars et al in 2018 which showed 3D high resolution ~ 30 ~ sequences provide knee articular cartilage imaging with high image quality (SNR, contrast, artifacts) in relatively short acquisition time, minimum artifacts and more accurate cartilage thickness measurement [6] . Delaram Shakoor et al in 2019 showed that the diagnostic performance of 3D MRI has statistically significantly improved and that current 3D MRI techniques provide comparable diagnostic performance to 2D MRI for depicting cartilage defects within the knee joint.…”
Section: Medial Tibial Plateausupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, 3D water excitation sequence was found to be better than 2D fat suppression sequence for cartilage over lateral tibial plateau. This study correlates well with the study done by Mokhtar Mars et al in 2018 which showed 3D high resolution ~ 30 ~ sequences provide knee articular cartilage imaging with high image quality (SNR, contrast, artifacts) in relatively short acquisition time, minimum artifacts and more accurate cartilage thickness measurement [6] . Delaram Shakoor et al in 2019 showed that the diagnostic performance of 3D MRI has statistically significantly improved and that current 3D MRI techniques provide comparable diagnostic performance to 2D MRI for depicting cartilage defects within the knee joint.…”
Section: Medial Tibial Plateausupporting
confidence: 91%
“…Fat suppression can be achieved with three methods: fat saturation, inversion-recovery imaging, and opposed-phase imaging [6] .…”
Section: Introductionmentioning
confidence: 99%
“…First, because of using a slice thickness of about 3mm, they suffer from partial-volume artifacts. Second, the difficulty to evaluate oblique and small structures because cartilage is a thin layer with a complex surrounding anatomical structure such as ligaments and tendons which are oriented oblique and difficult to assess with 2D sequences (5) . 3D high-resolution imaging is suggested to be an alternative of 2D imaging, since it provides isotropic or nearly isotropic 3D imaging which can be reconstructed in any desired orientation with contiguous thin slices in order to reduce partial volume artifact effects.…”
Section: Introductionmentioning
confidence: 99%